Pengembangan Media Pembelajaran Berbasis Android pada Materi Mengenal Sejarah Agama Buddha SMP di Kecamatan Gladagsari - Budayat Budayat; Endang Sri Rejeki; Sukisno Sukisno (Departement of Mathematics Education, 2023)
The advancement of science and technology has progressed rapidly, especially in the field of education. In this era, the world of education is evolving swiftly, marked by the development of learning media, including android-based learning tools. In the junior high schools of the Gladagsari district, there's still limited utilization or development of learning materials, particularly those based on android. The educational media currently in use consists of basic tools like PowerPoint, Google Classroom, and Google Sites.This situation has piqued the researcher's interest in conducting a study with the aim of developing android-based learning materials for junior high school students. This research employs the Research and Development methodology, following the ADDIE development model. Data is collected through interviews, questionnaires, and data checklists. The result of this research is an android-based learning media product focused on the history of the Buddhist religion for junior high schools in the Gladagsari district.This product has been evaluated by media experts, achieving an 80% approval rate, and subject matter experts, with a 97% approval rate. Furthermore, the feedback from students, with a 91% approval rate classified as